Inadequacy of Legal Protection against the Economic Exploitation of Children in Indonesia - Annisa Shiva Safira; Bambang Waluyo (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
Despite being regulated under Law No. 35 of 2014 on Child Protection, child labour remains a serious problem in Indonesia. Data from the Central Statistics Agency (BPS) indicate an increase in child labourers from 1.01 million in 2023 to 1.27 million in 2024, highlighting a persistent gap between legal norms and social realities. This study examines child labour through victimological and human rights perspectives, arguing that children are victims of structural exploitation legitimized by regulatory loopholes. Using a normative legal method with qualitative analysis, the research reviews national legislation, international legal instruments, and relevant court decisions. The findings reveal that structural poverty, weak institutional coordination, and the ambiguous regulation of “light work” under Article 69 of the Manpower Law constitute a legal loophole that normalizes child labour and obscures children’s victim status. Consequently, children are excluded from victim-centered remedies such as compensation and rehabilitation. The study concludes that effective protection requires concrete legal and policy reforms, including clarifying the scope of permissible work, strengthening inter-agency coordination, integrating UNCRC principles into labour regulation, and expanding family-based social protection to address the structural causes of child labour..